Distribution Optimization Using Ant Colony Optimization (ACO) Method Case Research: PT. Coca Cola Official Distributor of Surabaya Area - Rusindiyanto; Rahmawati, Nur; Sutejo , Muhammad Andriven Gozali (Nusantara Science and Technology Proceedings)
PT.Coca-Cola Amatil Indonesia is a manufacturing company that produces beverages such as soft drinks, tea, milk, juice, isotonic and mineral water, located in Pandaan. This company has a distribution area that is spread almost all over Indonesia. In the Surabaya area, the company has 30 kiosks/salesmen as partners. The distribution of products in the Surabaya area is done through Take Order (TO) sales. The final product is distributed to consumers through third parties. The purpose of this research is to determine the distribution route with the shortest distance. The distribution problem experienced by this company is better known as the Traveling salesman problem (TSP). TSP is a combinatorial problem where when the problems faced are increasingly complex, the time needed is also getting longer. Several methods for solving TSP have been proposed. One of the best is the metaheuristic method, one of which is Ant Colony Optimization (ACO). In this research, the ACO method is used to solve the TSP problems encountered. The routes generated from the ACO method are 41.3 km which is 9.03% shorter than the actual route.